2017
DOI: 10.3324/haematol.2016.155747
|View full text |Cite
|
Sign up to set email alerts
|

Targeted activation of the SHP-1/PP2A signaling axis elicits apoptosis of chronic lymphocytic leukemia cells

Abstract: Lyn, a member of the Src family of kinases, is a key factor in the dysregulation of survival and apoptotic pathways of malignant B cells in chronic lymphocytic leukemia. One of the effects of Lyn’s action is spatial and functional segregation of the tyrosine phosphatase SHP-1 into two pools, one beneath the plasma membrane in an active state promoting pro-survival signals, the other in the cytosol in an inhibited conformation and unable to counter the elevated level of cytosolic tyrosine phosphorylation. We he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Especially interesting is the evidence that inhibition of protein dephosphorylation is an integral part of chromatin-associated functions of nuclear PP2A inhibitor protein SET. Together with previous data indicating strong association of SET with histones, we speculate that this may generate spatially restricted inhibition of dephosphorylation of chromatin remodeling complexes and that SET modulation by emerging small molecule approaches 70 , may provide novel opportunities for targeting epigenetic gene regulation.…”
Section: Discussionsupporting
confidence: 76%
“…Especially interesting is the evidence that inhibition of protein dephosphorylation is an integral part of chromatin-associated functions of nuclear PP2A inhibitor protein SET. Together with previous data indicating strong association of SET with histones, we speculate that this may generate spatially restricted inhibition of dephosphorylation of chromatin remodeling complexes and that SET modulation by emerging small molecule approaches 70 , may provide novel opportunities for targeting epigenetic gene regulation.…”
Section: Discussionsupporting
confidence: 76%
“…Currently, partial crystal structures of CIP2A, PME-1, and SET are known [40][41][42], and there is already relatively good understanding of how each of these PIPs modulate PP2A activity [30,40,43]. Small-molecule SET inhibitors have already been identified, and they have shown promise in inhibiting oncogenic signaling and malignant cell behavior [21,32,[44][45][46]. In accordance with the major theme of this review, a recent study demonstrated that combination of SET targeting and tyrosine kinase inhibitor provides an effective therapeutic approach in human T-cell acute lymphoblastic leukemia [34].…”
Section: Therapeutic Targeting Of Pp2amentioning
confidence: 99%
“…On the other hand, SHP-1 exists in CLL cells as two distinct pools, one of which is bound to the Tyr-phosphorylated cytoplasmic tail of the transmembrane CLL marker CD5, most likely supporting pro-survival pathways, and the other that is located in the cytoplasm in an inactive form that can be reactivated by small molecules that disrupt the inhibitory intramolecular interactions. Importantly, the restoration of the activity of these two phosphatases has been reported to evoke CLL cell apoptosis by disrupting the phosphorylation-dependent pro-survival and antiapoptotic signaling network [13,62]. In this regard, we recently showed that compounds restoring the activity of PP2A and SHP-1, which is largely impaired in varied types of cancer, constrained kinase-orchestrated survival signaling pathways, thereby inducing apoptosis in CLL cells; notably, the use of such activators in combination with kinase inhibitors resulted in a dramatic synergistic effect [12,63], which may open a new avenue in the development of new therapeutic strategies.…”
Section: Imbalance Between Kinases and Phosphatases Activities: The Kmentioning
confidence: 99%
“…Furthermore, oxidation might directly induce/modulate kinase activity such as in Src family kinases (SFKs) or Akt serine-threonine kinase [6][7][8][9][10][11]. Translational studies have revealed the important link between oxidation and signal transduction pathways in both oncologic and benign hematological disorders [12][13][14][15][16][17][18][19][20][21]. In this review, we focus on models of globally distributed hematological diseases for which the link between intracellular signaling and oxidation has been recently reported.…”
Section: Introductionmentioning
confidence: 99%